PELATIHAN PEMBUATAN HANDWASH GEL EKSTRAK DAUN KEMANGI (OCIMUM SANCTUM L) SECARA MANDIRI UNTUK PENANGGULANGAN PEMUTUSAN RANTAI PENYEBARAN CORONA VIRUSE DISEASE -19 DI WILAYAH PATRANG TENGAH - Nafisah Isnawati,; Kustin, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Coronavirus is an infectious disease caused by the SARS-CoV-2 virus.Where that can be infect the respiratory system which causes the death of thousands people and becomes a big problem for many countries including Indonesia. Precaution the spread of virus is by washing hands, wearing masks, and keeping a distance. Handwash gel has an important role when we was washing hands. The purpose of the activity is to increase a skills and knowledge of making handwash gel in the Central Patrang area. Community dedication activities are using methods of increasing knowledge, training and practicing the manufacture and packaging of handwash preparations. The implementation of the activities is began with licensing in the local area, opening, pretest, material presentation, implementation of the manufacture and packaging of handwash gel. The output target of the activities is to be achieved that able to provide understanding and increase community productivity in the manufacture of handwash gel. The results of observations during the activity obtained positive results, the participants showed good attention to the material and implementation of making. therefore, the community dedication in Patrang area is running well.